2011
DOI: 10.1038/ncb2366
|View full text |Cite
|
Sign up to set email alerts
|

miR-34 miRNAs provide a barrier for somatic cell reprogramming

Abstract: Somatic reprogramming induced by defined transcription factors is a low efficiency process that is enhanced by p53 deficiency 1-5. To date, p21 is the only p53 target shown to contribute to p53 repression of iPSC (induced pluripotent stem cell) generation 1, 3, suggesting additional p53 targets may regulate this process. Here, we demonstrated that mir-34 microRNAs (miRNAs), particularly miR-34a, exhibit p53-dependent induction during reprogramming. mir-34a deficiency in mice significantly increased reprogrammi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
352
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 362 publications
(370 citation statements)
references
References 45 publications
12
352
0
Order By: Relevance
“…This finding reinforces the notion that p53 impairs reprogramming not exclusively through apoptosis or cell senescence [26]. Mechanistically, lincRNA-p21 blocks reprogramming by preserving high levels of H3K9me3 and CpG methylation at pluripotency genes.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…This finding reinforces the notion that p53 impairs reprogramming not exclusively through apoptosis or cell senescence [26]. Mechanistically, lincRNA-p21 blocks reprogramming by preserving high levels of H3K9me3 and CpG methylation at pluripotency genes.…”
Section: Discussionsupporting
confidence: 76%
“…We selected 51 lincRNAs previously reported to regulate embryonic stem cell (ESC) pluripotency (26) or differentiation (25) [22] and 16 p53-regulated lincRNAs [18] (Figure 1A). The rationale for choosing the latter group is that p53 is an important regulator of ESC differentiation and a major barrier for reprogramming [8].…”
Section: Functional Screening Reveals Roles Of Lincrnas In the Preipsmentioning
confidence: 99%
“…[21][22][23][24][25][26][27][28][29] Thus, we asked whether p53 is also activated in p63 À / À MEFs. However, neither p53 protein nor its sensitive targets p21 and miR34a/b/c, also known reprogramming barriers, [40][41][42][43] (Figure 5g). Moreover, the tumor suppressors p19-Arf and p16-Ink4A, which are known reprogramming barriers in mouse and human fibroblasts, 23,24 were shown to partially mediate skin and limb defects of p63 À / À mice.…”
Section: Resultsmentioning
confidence: 99%
“…24 Members of the miR-34 family have been suggested as critical regulators in regulation of cancer cell apoptosis and cell cycle arrest. 16,25,26 It has been recently reported that suppression of somatic cell reprogramming into pluripotent cells by miR-34a was due to their repression of pluripotency genes, 27 implying that miR-34a could have an important role in stem cell differentiation. Indeed, recent studies show that miR-34a has a role in neural 28 and megakaryocytic differentiation 29 and is a critical cell-fate determinant in early-stage dividing colon cancer stem cells.…”
Section: S Ir T 1 a C T A 2 T A G Lnmentioning
confidence: 99%